Evaluation of Beef Top Sirloin Steaks of Four Quality Grades Cooked to Three Degrees of Doneness - Brittany A. Olson; Emily A. Rice; Jessie Vipham; John M. Gonzalez; Lauren L. Prill; Lindsey N. Drey; Michael D. Chao; Travis O'Quinn (Meat and Muscle Biology, 2019)
The objective of this study was to evaluate the impact of USDA quality grade on beef eating quality of top sirloin steaks when cooked to multiple degrees of doneness (DOD). Beef top sirloin butts (N = 60; 15/quality grade) were collected to equally represent 4 quality grades [Prime, Top Choice (modest00 to moderate100), Low Choice, and Select]. Steaks were assigned to 1 of 3 DOD: rare (60°C), medium (71°C), and well-done (77°C). Steaks were allocated to either consumer sensory analysis, trained sensory analysis, fat and moisture analysis, or Warner-Bratzler shear force (WBSF). There were no interactions (P > 0.05) for all consumer ratings of palatability traits, indicating increases in DOD had the same impact across all quality grades. Prime steaks had greater (P < 0.05) juiciness ratings than all other quality grades, except for Top Choice. As DOD increased, consumer ratings and the percentage of steaks rated acceptable for each palatability trait decreased (P < 0.05; rare > medium > well-done). There was a quality grade × DOD interaction (P < 0.05) for trained sensory panel juiciness scores. When cooked to medium, Prime and Top Choice steaks were rated higher (P < 0.05) for juiciness than Low Choice and Select steaks, while there were no differences at all other DOD. Similar to consumer ratings, trained panel ratings of tenderness decreased (P < 0.05) as DOD increased (rare > medium > well-done). Lastly, there was no quality grade by DOD interaction (P > 0.05) for Warner-Bratzler shear force. These results indicate that regardless of the DOD top sirloin steaks are cooked to, quality grade had minimal impact on palatability. Therefore, it is unnecessary for consumers, retailers, and foodservice to pay premium prices for higher quality top sirloin steaks, as the same eating experience will be provided.